Determinants of Chronic Kidney Disease among Young Adults attending a Tertiary Care Hospital in Madurai- A Case-Control Study - Sridevi PN; Thirukumaran R; Kannan Muthuraman A; Arunkumar Yograj; Priya S; Hemamalini B (Healthline)
Introduction: As with other non-communicable diseases, chronic kidney disease (CKD) also is in a way at the top among the younger population. Apart from diabetes, hypertension, old age, family history of CKD other risk factors like smoking, alcohol, pesticide exposure, heavy metals also made them vulnerable to CKD. The focus on CKD in younger age groups is often overlooked; therefore, this study has been planned to address this gap. Objective: To determine the risk factors for chronic kidney disease among young adult patients <40 years of age. Method: An unmatched case control study was conducted in district hospital in Madurai. The study compared patients with chronic kidney disease aged under 40 (cases) from the Nephrology ward and outpatient with similar-aged controls without CKD from the Medicine ward, using routine eGFR calculations for diagnosis. The calculated sample size was 76, which was rounded up to 100 participants in both the case and control groups. Data collection was done by using semi-structured questionnaire. Univariate and multivariate analysis were used to predict the risk factors for young CKD patients. Results: The study predicted that rural population (OR-5.236, 95% CI-2.489- 11.014), family history of CKD (OR-29.590, 95% CI- 3.351-261.243), hypertension (OR-5.005, 95% CI-2.014-12.437), history of taking alternative medicine (OR- 5.136, 95% CI-1.745-15.117), and recurrent urinary tract infection (OR-11.460, 95% CI-2.288-57.444) were significantly associated risk factors for CKD. Conclusion: This study predicted hypertension, rural population, family history of CKD, history of recurrent urinary tract infection, alcohol consumption as significant risk factors for CKD. Hypertension, history of recurrent urinary tract infection, alcohol consumption were modifiable risk factors. By controlling these modifiable risk factors, the burden of CKD can be reduced. In addition this study predicted that, rural population was more vulnerable to CKD, so the screening service to these populations through primary health care approach is essential.